Perilaku Komunikasi Remaja Pemain Game Online ‘‘Mobile Legend” - Enelson, Fendi; Putra , Dilmai; Sari , Sapta (CV. Era Digital Nusantara, 2024)
Currently online games are very popular with almost all groups. Online games are interesting to play, in fact for some people online games have become a primary need. In the past, online games could only be enjoyed via a personal computer (PC), but as time goes by, now online games can be enjoyed anywhere and anytime via smartphone. This research aims to understand teenagers' communication behavior towards the online game